Synergistic Apoptotic Effect of Crocin and Paclitaxel or Crocin and Radiation on MCF-7 Cells, a Type of Breast Cancer Cell Line. (26th November 2015) - Vali, Faeze; Changizi, Vahid; Safa, Majid
Abstract : Background. Chemotherapy, radiotherapy, and surgery are routine treatments of breast cancer. However, these methods could only improve the living survival. Nowadays the combined therapy including herbals such as crocin is to study for improving breast cancer treatment. The purpose of this study was to evaluate the effects of crocin, paclitaxel, and radiation on MCF-7 cell. Methods. To evaluate the effect of crocin, paclitaxel, and radiation on survival rate of MCF-7 cells MTT assay was done. To investigate the apoptotic effect of experimental groups PI-flow cytometry was used and expression of apoptotic proteins (caspase-7, caspase-9, PARP, and p53) was studied by western blot. Results. This study revealed that the combined therapy of 0.01 µ mol/mL paclitaxel and 2.5 mg/mL crocin after 48 h could cause IC50 for MCF-7 cell line. This study showed that the combined therapy of 2 Gy gamma radiation with crocin could rise apoptosis in MCF-7 cell line from 21% (related to using 2 Gy gamma radiation alone) to 46.6%. Conclusion. Crocin and paclitaxel and crocin and gamma radiation had synergistic effect on MCF-7 cell line to get more significant apoptosis.